Pengaruh Gerak U-Turn terhadap Kinerja Lalu Lintas di Jalan D.I. Panjaitan - Wanto, Endra; Suhendra, Suhendra; Setiawan, Ari (Universitas Batanghari Jambi, 2024)
Jalan D. I. Panjaitan in the city of Jambi is a vital road with a 2 lane 2 way (2/2) road type, where there are some roads that use permanent road dividers and some that do not use road dividers. The condition of the road which includes residential areas, shops, schools, hospitals, places of worship, and so on causes road traffic to develop according to the conditions around the road. The aim of the research is to determine the effect of U-turn Volume and Degree of Saturation on Jl. D. I, Panjaitan, knows the level of service on Jl. D. I, Panjaitan. The conclusion is that based on the research results that have been calculated, it can be obtained that the U-turn volume influences the degree of saturation (DS) with a positive correlation, so the highest degree of saturation is obtained with a correlation coefficient value of 0.89. The coefficient value shows that the greater the U-turn volume. the greater the influence on the degree of saturation (DS). So the level of vehicle road service on Jl. DI Panjaitan with a road service level volume of 0.56 can have a service level of C. Where the flow is stable, but the speed of vehicle movement is controlled.